Hukum yang Berkeadilan Bagi Rakyat Indonesia dalam Perspektif Mahasiswa Fakultas Bahasa dan Seni Universitas Negeri Medan - Kanaya Azzahra; Aisyah Ashari; Laira Desti Natalia Saragih; Lisa Anggraini; Nurul Atikah; Rosa Putri Theresia Sinaga; Sri Yunita (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
This research aims to find out how the law is fair for the people of Indonesia, from the point of view of students at the Faculty of Languages ??and Arts, State University of Medan. The times, which are supported by globalization, make new laws exist and the Indonesian people are demanded to be able to adapt in the life of society, nation and state. Researchers conducted an online study by distributing questionnaires to respondents who were students of Indonesian Literature at Medan State University. This study adopted a research method in the form of a qualitative descriptive method. Therefore, students as the forerunner of law enforcement must take a role in this matter, and it is hoped that students will be able to have critical, analytical, innovative, and progressive thinking so that the essence of fair law enforcement can be achieved.